Evaluation of the Late-Life Disability Instrument (LLDI) in Low-Income Older Populations. (April 2014) - Vafaei, Afshin; Gomez, Fernando; Zunzunegui, Maria V.; Guralnik, Jack; Curcio, Carmen L.; Guerra, Ricardo; Alvarado, Beatriz E.
Objective: To assess the construct and convergent validity of the 16 items of the Late-Life Disability Instrument (LLDI) in Latin American seniors.Method: Exploratory and confirmatory factor analyses were performed to assess the factor structure of frequency and limitation sub-scales of the LLDI. ANOVA and t test were used to determine the convergent and construct validity of the LLDI by exploring associations with physical performance tests, mobility limitations, depression, cognition, self-reported health, as well as with sex, education, and income.Results: Factor analysis resulted in one-factor solution and acceptable model fit. Participants with better physical function, less mobility limitations, better self-reported health, and intact cognition reported more frequent activities and fewer limitations, indicating good convergent and construct validity of our measure.Conclusion: LLDI is a good instrument to assess disability in low-income populations. Further research is needed to include culturally acceptable activities for the frequency sub-scale.